The Predictive Capacity of the Buffalo Concussion Treadmill Test After Sport-Related Concussion in Adolescents - Haider, Mohammad N.; Leddy, John J.; Wilber, Charles G.; Viera, Kaitlin B.; Bezherano, Itai; Wilkins, Kimberly J.; Miecznikowski, Jeffrey C.; Willer, Barry S. (Frontiers in Neurology, 2019)
The Buffalo Concussion Treadmill Test (BCTT) identifies the heart rate threshold (HRt) of exercise tolerance in concussed patients. A previous study found that an absolute HRt of <135 bpm was associated with prolonged recovery (>30 days) from sport-related concussion (SRC). In this study, we assessed the relationship of ΔHR (difference between resting HR and HRt) and recovery from SRC. Using a retrospective cohort design, we compared acutely (<10 days) concussed adolescents who were prescribed either (1) relative rest (RG, n=27, 15.2±1 years, 33% female, median 17 days to recovery, ΔHR=69.6±28 bpm), (2) a placebo-stretching program (PG, n=51, 15.4±2 years, 49% female, median 17 days to recovery, ΔHR=60.9±22 bpm), or (3) sub-threshold aerobic exercise (AG, n=52, 15.3±2 years, 46% female, median 13 days to recovery, ΔHR =62.4±26 bpm). Linear regression showed that ΔHR significantly correlated with duration of clinical recovery for RG (p=0.012, R2 =0.228) and PG (p=0.011, R2 =0.126) but not for AG (p=0.084, R2 =0.059). ΔHR values were significantly lower in participants with prolonged recovery (> 30 days) in RG (p=0.01) and PG (p=0.04). A ΔHR of ≤ 50 bpm on the BCTT is 73% sensitive and 78% specific for predicting prolonged recovery in concussed adolescents who were prescribed the current standard of care (i.e., cognitive and physical rest).